The Relevance of the Hadith 'A Woman is Married for Four Things' in Contemporary Muslim Mate Selection: A Maudhu'i Approach - Ghina Sofia Mahfuzah; Hairul Hudaya; Salma Ellya (At-Ta'lim : Media Informasi Pendidikan Islam, 2025)
ENGLISH: The Relevance of the Hadith 'A Woman is Married for Four Things' in Contemporary Muslim Mate Selection: A Maudhu'i ApproachObjective: This study aims to analyze the hadith “Women Are Married for Four Reasons” using a thematic approach and examine its relevance in the choice of a spouse in contemporary Muslim society. Method: This study uses a Maudhui approach, collecting related hadiths, analyzing their sanad and matan, and exploring the social context behind the hadith. Results: Although wealth, lineage, and beauty are essential, religion should be the top priority in choosing a spouse because religion is directly related to happiness and stability in the household. In addition, choosing a spouse based on religion is not only a matter of spirituality, but also of morals, emotional maturity, and readiness to build a household. Conclusion: The Maudhui approach offers a more comprehensive understanding of the message of the hadith for fostering a harmonious and sustainable Muslim family. Contribution: This research provides new insights into understanding the message of the hadith “Women are married for four reasons,” as well as its relevance in the social and cultural context of contemporary Muslim society.INDONESIAN: Relevansi Hadis “Wanita Dinikahi Karena Empat Perkara” dalam Pemilihan Pasangan Muslim Kontemporer: Sebuah Pendekatan Maudhui.Tujuan: Penelitian ini bertujuan untuk menganalisis hadis "Wanita Dinikahi Karena Empat Perkara" dengan pendekatan Maudhui (tematik) dan melihat relevansinya dalam pemilihan pasangan di masyarakat Muslim kontemporer. Metode: Penelitian ini menggunakan pendekatan Maudhui, dengan mengumpulkan hadis-hadis terkait, menganalisis sanad dan matan, serta menggali konteks sosial yang melatarbelakangi hadis tersebut. Hasil: Meskipun harta, keturunan, dan kecantikan penting, agama harus menjadi prioritas utama dalam memilih pasangan karena agama berhubungan langsung dengan kebahagiaan dan kestabilan rumah tangga. Selain itu, memilih pasangan berdasarkan agama tidak hanya menyangkut spiritualitas, tetapi juga akhlak, kedewasaan emosional, dan kesiapan membangun rumah tangga. Kesimpulan: Pendekatan Maudhui dalam memberikan pemahaman yang lebih luas tentang pesan hadis untuk membangun keluarga Muslim yang harmonis dan berkelanjutan. Kontribusi: Penelitian ini memberikan wawasan baru dalam pemahaman pesan hadis "Wanita Dinikahi Karena Empat Perkara", serta relevansinya dalam konteks sosial dan budaya masyarakat Muslim kontemporer.